2015
DOI: 10.1590/1516-1439.286114
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stress Cracking of Poly(3-hydroxibutyrate) Under Contact with Sodium Hydroxide

Abstract: Environmental stress cracking (ESC) is one of the most important causes of polymer premature failure, occurring when a combination of mechanical load and an aggressive fluid is applied. The phenomenon is well know by polymer producers and product designers but its mechanisms are not very well understood. Although the ESC effects of many commercial polymers are well known, this type of failure in biopolymers were not studied yet. In the current work, the stress cracking behaviour of poly(3-hydroxybutyrate) (PHB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…This important mechanism of degradation is not often taken into account in the case of biodegradable polymers. One study by Farias et al [357] showed that sodium hydroxide may act as a strong stress cracking agent for PHBV copolymers, significantly affecting the mechanical properties. SEM imaging confirmed that catastrophic failure was associated with extensive surface damage.…”
Section: Mechanical and Other Effects On Biodegradable Polymer Degradationmentioning
confidence: 99%
“…This important mechanism of degradation is not often taken into account in the case of biodegradable polymers. One study by Farias et al [357] showed that sodium hydroxide may act as a strong stress cracking agent for PHBV copolymers, significantly affecting the mechanical properties. SEM imaging confirmed that catastrophic failure was associated with extensive surface damage.…”
Section: Mechanical and Other Effects On Biodegradable Polymer Degradationmentioning
confidence: 99%
“…[2][3][4] Structural faults, thermal stress, lack of mechanical resistance, environmental stress, working temperature above tempering (which could lead to the phase transition) could be considered the main reasons for fracture and deformation failure of molded parts. [5][6][7] Nikforooz et al 8 have studied fatigue behavior of laminated glass fiber-reinforced polyamide. In contrast to the behavior of unidirectional laminates, glass/polyamide laminates had a superior fatigue resistance compared to the glass/epoxy composite.…”
Section: Introduction *mentioning
confidence: 99%
“…PHB is inherently a non-toxic material and it is considered biocompatible, being used in medical applications like prosthesis, suture threats and devices for drugs release inside the human body [10][11] . The general uses of PHB in replacement of ordinary plastics are growing, including applications like packing and other short life products like cups and cutleries for fast food restaurants.…”
Section: Introductionmentioning
confidence: 99%